2010
DOI: 10.1073/pnas.0912376107
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a recent increase in forest growth

Abstract: Forests and their soils contain the majority of the earth's terrestrial carbon stocks. Changes in patterns of tree growth can have a huge impact on atmospheric cycles, biogeochemical cycles, climate change, and biodiversity. Recent studies have shown increases in biomass across many forest types. This increase has been attributed to climate change. However, without knowing the disturbance history of a forest, growth could also be caused by normal recovery from unknown disturbances. Using a unique dataset of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
282
2
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(316 citation statements)
references
References 45 publications
27
282
2
5
Order By: Relevance
“…Inventory data show increased forest growth rates in eastern North America (McMahon et al, 2010), potentially due to recent changes in climate, nutrient deposition, or community structure. Similar increases in tropical (Lewis et al, 2009) and temperate (Salzer et al, 2009, Urbanski et al, 2007Pilegaard et al, 2011;Dragoni et al, 2011) forest carbon uptake have been reported (but see Fahey et al, 2005), and have been linked to changes in the growing season length, and vegetation dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Inventory data show increased forest growth rates in eastern North America (McMahon et al, 2010), potentially due to recent changes in climate, nutrient deposition, or community structure. Similar increases in tropical (Lewis et al, 2009) and temperate (Salzer et al, 2009, Urbanski et al, 2007Pilegaard et al, 2011;Dragoni et al, 2011) forest carbon uptake have been reported (but see Fahey et al, 2005), and have been linked to changes in the growing season length, and vegetation dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Forest ecosystems are hypothesized to constitute a large part of this sink and to sequester C due to their regrowth and atmospheric CO 2 fertilization (Houghton, 2003;Janssens et al, 2003;McMahon et al, 2010). In order to test this hypothesis and to assess the strength of this feedback, Free Air CO 2 Enrichment (FACE) experiments in aggrading temperate forests and plantations were initiated.…”
Section: Introductionmentioning
confidence: 99%
“…They find that climatic change has a generally positive impact on forest productivity when water is not limiting. McMahon, Parker, and Miller (2010) estimate 6 that the Northeast U.S forest is growing at a much faster rate than expected and attribute this to rising levels of atmospheric CO2, higher temperatures and longer growing seasons. Foster et al (2010) argues to the contrary that past tree mortality could explain the difference in rates.…”
Section: Forestsmentioning
confidence: 99%